2016
DOI: 10.3928/01484834-20160516-05
|View full text |Cite
|
Sign up to set email alerts
|

Prelicensure Baccalaureate Nursing Students' Perceptions of Their Development of Clinical Reasoning

Abstract: Understanding students' perceptions of learning benefits nurse educators in planning nursing program curricula to enhance and facilitate the development of clinical reasoning. [J Nurs Educ. 2016;55(6):329-335.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Many researchers used the terms clinical decision‐making and clinical judgment interchangeably . Shaban stated the terms “essentially describe the same phenomena” (para.…”
Section: Surrogate Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers used the terms clinical decision‐making and clinical judgment interchangeably . Shaban stated the terms “essentially describe the same phenomena” (para.…”
Section: Surrogate Termsmentioning
confidence: 99%
“…During a crisis, the nurse must be able to prioritize responsibilities and multitask to achieve results quickly. Confidence in one’s knowledge, psychomotor, and communication skills, and the ability to think and make decisions is essential to making good judgments . Etheridge’s longitudinal study of new nurses concluded self‐confidence, relationships with others, learning responsibility, and thinking critically facilitates the development of sound clinical judgment.…”
Section: Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlighting the complexity of clinical reasoning and decision‐making, recent studies of undergraduate students and experienced clinicians suggest that reasoning involves conceptual (what), strategic (how), conditional (why) and metacognitive knowledge (Pintrich, ; Potthoff et al., ; Rodriguez, Rhodes, Miller, & Shah, ; Schmidmaier et al., ). It has been reported that, with experience, clinicians can become more aware of these various forms of knowledge, more knowledgeable and aware of their own thinking, and better able to monitor, control and regulate their cognition (Bucknall et al., ; Herron, Sudia, Kimble, & Davis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Educators now recognise the role of undergraduate curriculum in building competence in clinical reasoning and decision‐making (Bucknall et al., ; Herron et al., ). Attention has also been given to how this emerging expertise is acquired in clinical environments, with distinctions made between technical and nontechnical skills (NTS) and how these capabilities are developed (Forsberg, Ziegert, Hult, & Fors, ; Herron et al., ; Johnsen, Fossum, Vivekananda‐Schmidt, Fruhling, & Slettebø, ). The nontechnical skills involved in CDM have been defined as the cognitive and interpersonal skills that complement technical knowledge in support of safe, effective and efficient care (Gordon, Fell, Box, Farrell, & Stewart, ).…”
Section: Introductionmentioning
confidence: 99%